Một số dạng thiên tai thường xảy ra ở tỉnh Lào Cai. Cách phòng tránh - Nguyễn, Duy Hưng (2011)
Tác giả: Nguyễn Duy Hưng; Lưu Minh Hải; Phạm Quang Nội; Phạm Đức Dũng; Nguyễn Đức Vượng -- Từ khóa: Thiên tai; Biện pháp phòng tránh